Electrode and manufacturing method and application thereof
By forming a straight hole structure in the electrodes of a lithium-ion battery, the problem of increased energy density but decreased charging capacity and power performance in the prior art is solved, and higher battery performance and higher industrial efficiency are achieved.
Patent Information
- Application Number
- CN202411904162.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
While increasing the energy density, existing lithium-ion batteries are difficult to maintain or improve charging capacity, power performance and electrolyte infiltration rate, and have low production efficiency and insufficient life and safety.
An electrode with a straight hole structure and its manufacturing method are adopted. By inserting a hole-making needle made of flexible fibers into the electrode paste, the hole-making needle is pulled out during the drying process to form a vertical hole structure, which significantly reduces the torsion of the pores and improves the charging capacity and power performance of the battery.
On the basis of ensuring energy density, it has significantly improved the charging capacity, power performance and electrolyte infiltration rate of the battery, improved production efficiency, extended the battery life and improved safety.
Smart Images

Figure CN119695082A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to an electrode and a manufacturing method and application thereof. Background Art
[0002] As lithium-ion batteries gradually enter thousands of households, people have higher and higher demands on battery performance, especially in terms of energy density, fast charging capability and high-power discharge capability. In order to meet these demands, lithium-ion battery designers are constantly exploring new design ideas and technical means.
[0003] In the process of improving the energy density of batteries, single cells are usually made larger and electrodes are made thicker. However, this design also brings a series of problems. Due to the porous structure characteristics of the electrode, the electrolyte needs to enter all pores and fully infiltrate all active materials of the electrode to ensure that lithium ions are fully conductive. When the electrode becomes larger and thicker, the path of the electrolyte infiltrating the electrode increases and the degree of tortuosity increases, which is not conducive to the transmission of lithium ions, resulting in an increase in the internal resistance of the battery, thereby reducing the fast charging ability and power of the battery. When the infiltration is poor, it will affect the life and safety of the battery.
[0004] How to ensure energy density without reducing charging capacity and power, or even further improve these indicators, is the focus of research by practitioners. The existing technologies mainly include the following:
[0005] 1. Thin electrode design: When designing fast-charging batteries, the transmission path of lithium ions inside the electrode can be shortened by adopting a thin electrode design. However, this method will reduce the proportion of active materials, thereby limiting the energy density of the battery.
[0006] 2. Low compaction density design: By reducing the compaction density of the electrode, the porosity can be increased, thereby reducing the tortuosity of the lithium ion transmission path. However, this method will also lead to a decrease in the proportion of active materials, affecting the energy density of the battery.
[0007] 3. Etching holes on the electrode surface: By mechanically or laser etching holes on the electrode surface, the electrolyte infiltration channel can be increased and the transmission efficiency of lithium ions can be improved. However, when using mechanical drilling, very high pressure is required to break through the active material on the electrode surface, making the depth of the drilling uncontrollable. In addition, due to the extrusion of the active material at the drilling position, the active material around the hole is raised, affecting the surface flatness and the uniformity of the current distribution in the cycle, which is easy to cause lithium precipitation; on the opposite side of the drilling position, due to the extrusion effect, there will inevitably be excess material accumulation, resulting in protrusions or shedding. Once the electrode is punched through, it is easy to produce metal burrs and foreign particles, which are easy to puncture the diaphragm, resulting in poor end grains or self-discharge, and waste active materials. If the size of the hole is too large, it will affect the battery energy density. If the size of the hole is too small, it will pose a huge challenge to the material of the puncher. When using laser, the advantage is that the size, position, and depth of the hole are controllable, but there is still a large thermal radiation affected zone during high-temperature ablation, and the active material in the thermal radiation zone is destroyed, affecting the electrical properties and energy density, and wasting materials. In addition, the molten beads and slag produced by laser ablation at high temperatures may cause short circuits and self-discharge. Finally, the efficiency of laser ablation is a huge drawback, making industrialization extremely difficult.
[0008] 4. 3D printed electrodes: 3D printing technology can precisely control the shape and structure of electrodes. Although it does not waste materials, the efficiency of 3D printing is extremely low, the cost of the print head is extremely high, and large-scale industrialization is extremely difficult.
[0009] In response to the surface unevenness and powder loss problems caused by laser or mechanical punching during the punching process, CN111370645A discloses a method for processing a pole piece by extruding holes on the surface of a liquid slurry and filling it with fillers. Although this method eliminates a large number of powder loss problems and improves surface flatness, it still faces several problems during implementation: when solid fillers such as metal probes are used, after the slurry is dried and solidified, the metal probe is tightly wrapped by materials such as active substances / binders, making it difficult to achieve non-destructive removal. If you try to pull it out by force, it will not only cause the active material to fall off and cause powder loss, but in some cases, the metal probe may not be pulled out at all due to the tight fit. If a pore-forming agent is selected as a filler, although it should theoretically leave holes during the volatilization process, due to the extrusion effect of the liquid slurry, the holes formed after drying are often not ideal vertical channels, but present a tortuous shape. This type of pore structure is not only not conducive to the uniform infiltration of the electrolyte, but also prolongs the path for the electrolyte to penetrate into the electrode, increases the tortuosity of the infiltration, and thus has an adverse effect on the performance of the lithium-ion battery. CN106531961A discloses a method for symmetrically and evenly distributing grooves on the surface of the active material coating on both sides of the pole piece by rolling with a specific boss roller or cold pressing with a specific boss flat plate. The rolling or cold pressing process can easily cause certain damage or deformation to the pole piece material, especially when the pressure used is large, the damage or deformation is more obvious, thereby affecting the conductivity and mechanical strength of the pole piece, and then adversely affecting the performance and life of the battery. Not only that, because the compaction density of the boss extrusion area is higher than that of the unextruded area, the compaction density of the active material area of the electrode is uneven, which makes the current density uneven, and also makes it difficult for the electrolyte to pass through the extruded area, which is not conducive to the performance of the battery cell. At the same time, if the pressure is too small, the depth of the groove cannot be guaranteed, thereby affecting the infiltration effect of the electrolyte. CN109817895A discloses an electrode preparation method in which micropores are punched on the surface of the pole piece dressing area by a laser mechanism when the surface of the pole piece dressing area is in a gel state. Although laser drilling technology can punch micropores on the surface of the electrode dressing area, heat and stress will be generated during the laser drilling process, which can easily damage the active material on the surface of the electrode, and the shape of the micropores is easily deformed, which in turn affects the performance of the battery. The evaporation point of the solvent in the dressing area is low, usually within 150°C, while the laser drilling temperature of the active material is high, usually requiring 400-500°C, or even higher. Most of the heat generated by the laser will be absorbed and volatilized by the solvent until all the solvent in the range is evaporated, and then the laser drilling will be turned into a dry state, which not only wastes energy, but also reduces the drilling efficiency. At the same time, high-temperature ablation cannot be avoided during the laser drilling process of this method, resulting in foreign matter such as molten beads and slag. In addition, the expensive cost and operational complexity of laser drilling equipment also limit the widespread application of this method in industrial production.
[0010] In summary, existing technologies have many limitations in improving the performance of lithium-ion batteries. How to ensure energy density while not reducing or even improving the battery's charging capacity and power, improving industrialization efficiency, and improving battery life and safety are still technical problems that need to be solved in the field of lithium-ion batteries. Summary of the invention
[0011] In view of the many limitations of existing technologies in improving the performance of lithium-ion batteries, the present invention proposes an innovative solution, aiming to provide an electrode with a straight pore structure and a method for manufacturing the same. The core goal of the invention is to significantly improve the battery's charging capacity, power performance, and electrolyte infiltration rate, while ensuring high energy density, and to improve production efficiency.
[0012] The traditional high compaction density design leads to low electrode porosity, while high loading makes the electrode thicker and the pore tortuosity increases, which in turn leads to problems such as increased battery internal resistance, reduced fast charging capability, and limited power performance. In addition, the electrolyte faces difficulties in infiltrating these high-tortuosity pores, and it often takes a long time to complete the infiltration, which may not only lead to poor battery infiltration, but also reduce production efficiency.
[0013] To solve the above problems, the present invention designs an electrode with a straight pore structure, which significantly reduces the tortuosity of the pores, thereby improving the charging capacity and power performance of the battery, while allowing the electrolyte to more quickly and fully infiltrate the electrode.
[0014] To achieve this innovative design, the present invention proposes a new electrode manufacturing method. This method can efficiently form an electrode with a straight hole structure, greatly improving production efficiency, and the manufacturing method is different from existing mechanical punching, laser etching or 3D printing technologies, avoiding the defects that these technologies may bring, greatly improving the life and safety of the battery. At the same time, the method of the present invention avoids subtractive methods such as punching, achieving zero waste of raw materials. In addition, the method is also highly controllable and flexible, and the size, shape and distribution of the straight holes can be adjusted according to actual needs to further optimize the performance of the battery.
[0015] The following is the specific technical solution of the present invention:
[0016] In a first aspect, the present invention provides a method for manufacturing an electrode, comprising the following steps:
[0017] S1, coating the electrode slurry on the surface of one side of the current collector using a wet process;
[0018] S2, vertically immersing a pore-making needle made of flexible fibers into the electrode slurry;
[0019] S3, drying the electrode slurry;
[0020] S4, when the liquid content in the electrode slurry is 5-10wt%, the pore-forming needle is pulled out, and after the electrode slurry is completely dried, an active material layer with vertical pores is formed on the surface of the current collector;
[0021] S5, after coating the electrode slurry on the surface of the other side of the current collector, repeat the above steps S2-S4 to obtain an electrode, which includes a current collector and active material layers located on both sides of the current collector.
[0022] In step S2, since the electrode slurry is fluid at this time, the pore-making needle can be easily immersed in the slurry, and due to the effect of gravity, it can be vertically distributed in the slurry according to the number of holes per unit area.
[0023] In step S4, when the liquid content in the electrode slurry is 5-10wt%, the electrode slurry is about to be completely dry, and the electrode still contains a certain amount of solvent. The electrode slurry has a certain flexibility. When the hole-making needle is pulled out, the electrode slurry will not wrap the hole-making needle, thereby causing the hole-making needle to be unable to be pulled out or damaged. At the same time, it will not cause the vertical hole to collapse.
[0024] Furthermore, the vertical cross section of the pore-making needle can be one or more shapes such as circular, rectangular, diamond, triangular, etc., preferably circular. When the vertical cross section is circular, the diameter is preferably between 1-500 μm.
[0025] The appropriate current collector is selected according to the positive and negative electrodes of the electrode. Generally, when the electrode is a positive electrode, the current collector is preferably aluminum foil; when the electrode is a negative electrode, the current collector is preferably copper foil.
[0026] Furthermore, the immersion area of the pore-making needle is 0.01%-10% (preferably 0.03%-3%) of the electrode slurry area. If the proportion is less than 0.01%, the improvement of charging capacity and discharge power is small, and when the proportion is greater than 10%, although the improvement of charging capacity and discharge power is large, the energy density decreases greatly. Therefore, the preferred proportion is 0.01%-10%, so that the battery has excellent comprehensive performance.
[0027] Furthermore, the surface of the pore-making needle has a hydrophobic coating or an oleophobic coating, and the hydrophobicity or oleophobicity of the coating is opposite to the hydrophobicity or oleophobicity of the electrode slurry, thereby facilitating the removal of the pore-making needle.
[0028] Flexible fiber is a material for preparing hole-making needles because it is easy to operate and does not easily damage the verticality of the hole. In terms of material, one or more of engineering plastic fibers such as PET, PP, PTFE, or high-strength materials such as glass fiber and carbon fiber can be selected.
[0029] Compared with the pore-forming needles made of rigid materials, the flexible fiber pore-forming needles show significant advantages in the entire operation process from insertion to extraction. The rigid pore-forming needle must always maintain a strict vertical state during the process of inserting the electrode slurry until it is completely pulled out, and it is also necessary to ensure a vertical upward movement trajectory when pulling out to avoid adverse effects on the verticality of the hole. However, the electrode slurry is fluid, and its density gradually increases during the drying process, which makes it a huge challenge for the rigid pore-forming needle to overcome the slurry extrusion to maintain a vertical posture. In the industrial production process, the electrode is produced on the assembly line. When the pore-forming needle is pulled out, the electrode continues to move forward, which requires the application of upward and forward forces at the same time, making it extremely difficult to control the rigid pore-forming needle to maintain a vertical posture, which often causes the pore-forming needle to tilt or even collapse, seriously affecting the quality and production efficiency of the product. In contrast, the flexible fiber pore-forming needle, with its good flexibility and elasticity, can more effectively adapt to the fluidity and density changes of the electrode slurry. During the insertion process, the flexible fiber can deform appropriately to follow the flow of the slurry, thereby reducing the insertion resistance; when pulled out, its elastic recovery ability can ensure that the pore-making needle can be smoothly and vertically separated from the slurry, forming a pore structure with good verticality. This feature makes the flexible fiber pore-making needle more stable and controllable in industrial production, providing a strong guarantee for the precise preparation of electrodes.
[0030] Furthermore, the immersion depth of the pore-forming needle is adjusted by a plurality of motion joints. Furthermore, the motion joints can also be used to adjust the relative speed between the pore-forming needle and the electrode slurry. The motion joints and the pore-forming needle can be integrated in the pore-forming system.
[0031] Preferably, the pore-forming system has two upper and lower rows of pore-forming needles, and the motion joint is located at both ends of the pore-forming system and in the middle of the upper and lower rows of pore-forming needles.
[0032] In a second aspect, the present invention provides an electrode prepared by the method described in the first aspect.
[0033] In a third aspect, the present invention further provides a battery, comprising the electrode described in the second aspect.
[0034] In the process of battery design, the present invention pays special attention to the problem of lithium ion precipitation at the negative electrode, which may threaten the safety and stability of the battery. To this end, the present invention proposes two innovative solutions:
[0035] 1. The positive electrode is perforated, and the negative electrode remains intact: In this solution, the positive electrode is prepared by the method described in the first aspect of the present invention, and includes a carefully designed vertical pore structure to optimize the lithium ion transmission path. The negative electrode maintains the traditional structure without perforations. This design can improve the charging efficiency and discharge performance to a certain extent while ensuring the safety of the battery.
[0036] 2. Both the positive and negative electrodes are perforated, and the positive electrode aperture is not less than the negative electrode aperture: In this scheme, both the positive and negative electrodes are prepared by the method described in the first aspect of the present invention, and both contain vertical pore structures. In particular, the aperture of the positive electrode is designed to be greater than or equal to the aperture of the negative electrode, and the centers of the holes are completely aligned. This design not only ensures the safety and stability of the battery, but also more effectively improves the fast charging capability and power density.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. The method of the present invention can efficiently form an electrode with a straight hole structure, greatly improving the production efficiency. The straight holes produced are flat, have no squeezing effect on the active material and no high-temperature ablation, thereby greatly improving the life and safety of the battery.
[0039] 2. The present invention proposes inserting a pore-forming needle made of flexible fibers during wet coating and pulling it out during the drying process, thereby forming vertical holes on the electrode surface; after the hole is filled with electrolyte, the wetting path can be greatly shortened; at the same time, the transmission path of lithium ions is also shortened, which can greatly improve the charging capacity and discharge power of the battery.
[0040] 3. The method of the present invention avoids material reduction methods such as punching, thereby achieving zero waste of raw materials.
[0041] 4. The method of the present invention is highly controllable and flexible, and the size, shape, depth and distribution of the straight holes can be adjusted according to actual needs to further optimize the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a structural schematic diagram of an embodiment of the battery cell structure of the present invention.
[0043] Figure 2 Schematic diagram of making holes for electrodes: Figure 2 A is the pore-making needle immersed in the electrode slurry; Figure 2 B is the hole-making needle pulling out the electrode slurry.
[0044] Figure 3 Schematic diagram of the pore-making system structure.
[0045] Figure 4 This is a schematic diagram of the electrode surface after pore formation in the present invention.
[0046] Figure 5 This is a schematic diagram of the continuous production of electrode pore formation according to the present invention.
[0047] Figure 6 is a schematic diagram of the structure of the pore-making needle in a vertical section, where Figure 6 A has a circular cross section. Figure 6 B is a rectangular cross section, Figure 6 C is a diamond cross section, and Figure 6 D shows a triangular cross section.
[0048] Figure 7 It is a schematic cross-sectional view of a specific embodiment of the electrode of the present invention in the thickness direction.
[0049] Figure 8 FIG. 4 is a schematic cross-sectional view of another specific embodiment of the electrode of the present invention in the thickness direction.
[0050] Fig. 9 FIG. 4 is a schematic cross-sectional view of another specific embodiment of the electrode of the present invention in the thickness direction.
[0051] Fig.10 FIG. 4 is a schematic cross-sectional view of another specific embodiment of the electrode of the present invention in the thickness direction.
[0052] Fig.11 FIG. 4 is a schematic cross-sectional view of another specific embodiment of the electrode of the present invention in the thickness direction.
[0053] Description of reference numerals:
[0054] 1. Cell structure; 2. Negative electrode sheet; 3. Positive electrode sheet; 21. Negative current collector; 22. Negative active material layer; 31. Positive current collector; 32. Positive active material layer; 4. Pore-making system; 41. Pore-making needle; 42. Motion joint; 5. Current collector; 6. Electrode slurry. DETAILED DESCRIPTION
[0055] In order to enable those skilled in the art to better understand the technical solutions in this application, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of this application, rather than all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.
[0056] All descriptions of parts and proportions in this specification are by weight unless otherwise specified.
[0057] In this specification, total pore area ratio=number of pores per unit area×area of a single pore.
[0058] In this specification, the "cross-sectional area" refers to the area perpendicular to the thickness direction.
[0059] In this specification, a "vertical cross section" refers to a plane perpendicular to the thickness direction.
[0060] Reference Figure 1, a battery cell structure 1, the battery cell structure 1 comprises alternately stacked positive electrode sheets 3 and negative electrode sheets 2. The battery cell structure has N layers of negative electrode sheets, N-1 layers of positive electrode sheets, and N≥2. Figure 1 It is shown that when N=2, the battery structure 1 includes 2 layers of positive electrode sheets 3 and 3 layers of negative electrode sheets 2. When N=3, the battery structure has 3 layers of positive electrode sheets and 4 layers of negative electrode sheets ( Figure 1 ), and so on.
[0061] The positive electrode sheet 3 includes a positive electrode current collector 31 and a positive electrode active material layer 32 located on both sides of the positive electrode current collector 31. The above-mentioned current collector is a foil material, which can be a metal such as aluminum and copper. The positive electrode current collector 31 is preferably an aluminum foil. The positive electrode active material layer 32 includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material is lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, lithium iron manganese phosphate, lithium-rich manganese, Na x One or more of MO2 layered oxide (M is mainly one or more transition metal elements), Prussian blue analogs, and sodium salts of polyanionic compounds. The general formula of the above-mentioned Prussian blue analogs is A x M1[M2(CN)6] 1-y □ y nH2O (0≤x≤2, 0≤y<1, n>0), where A is an alkali metal, such as Na + , K + etc.; M1 and M2 are transition metal ions with different coordinations (wherein M1 is coordinated with N and M2 is coordinated with C), such as Mn, Fe, Co, Ni, Cu, Zn, Cr, etc.; □ is a [M2(CN)6] vacancy. Usually, when the positive electrode sheet 3 does not curl, there may be a certain difference in the thickness of the positive electrode active material layer 32 on both sides of the second current collector 31. Preferably, the thickness of the positive electrode active material layer 32 on both sides of the current collector is the same. The preparation of the positive electrode sheet can usually adopt a wet process, and the electrode slurry used is a positive electrode active slurry, which is obtained by mixing the positive electrode active material layer with a solvent. The type and amount of solvent added can be adjusted according to the formula of the positive electrode active material layer and the needs of the wet process.
[0062] The negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 located on both sides of the negative electrode current collector 21. The above-mentioned current collector is a foil material, which can be a metal such as aluminum and copper. The negative electrode current collector 21 is preferably a copper foil. The negative electrode active material layer 22 includes a negative electrode active material, a conductive agent and a binder. The negative electrode active material can be one or more of graphite, silicon material, hard carbon, soft carbon, lithium metal, sodium metal, and other alloying materials. Usually, when the negative electrode sheet 2 does not curl, the thickness of the negative electrode active material layer 22 located on both sides of the negative electrode current collector 21 may have a certain difference. Preferably, the thickness of the negative electrode active material layer 22 located on both sides of the current collector is the same. The preparation of the negative electrode sheet can usually adopt a wet process, and the electrode slurry used is a negative electrode active slurry, which is obtained by mixing the negative electrode active material layer with a solvent. The type and amount of the solvent can be adjusted according to the formula of the negative electrode active material layer and the wet process requirements.
[0063] Reference Figure 2-Figure 3 In the process of manufacturing the electrode in the embodiment, a pore-making system 4 is used, which has a plurality of pore-making needles 41, which are made of flexible fibers. The arrangement of the pore-making needles is designed according to the number of holes per unit area on the active material layer. The vertical cross-section of the pore-making needles made of the flexible fibers can be one or more shapes such as circular, rectangular, diamond, triangular, etc. (see Figure 6 When the vertical cross section is circular, the diameter is preferably between 1 and 500 μm.
[0064] In one example, the surface of the pore-forming needle has a hydrophobic coating or an oleophobic coating, and the hydrophobicity or oleophobicity of the coating is opposite to the hydrophobicity or oleophobicity of the electrode slurry, thereby facilitating the subsequent removal of the pore-forming needle.
[0065] In another example, the pore-forming system has a plurality of motion joints 42, which are used to adjust the immersion depth of the pore-forming needle to insert / extract the pore-forming needle from the electrode slurry. Figure 3 As shown, it is located at both ends of the pore-making system and the upper part of the pore-making needles 41 to be immersed in the electrode slurry. In order to maintain the stability of the pore-making system, the pore-making needles 41 are usually designed into two rows, and the motion joints are located at both ends and in the middle of the pore-making needles 41 in the upper and lower rows.
[0066] Reference Figure 2 , combined with Figure 3 , the method for manufacturing an electrode in an embodiment comprises the following steps:
[0067] (1) coating the electrode slurry 6 on the surface of one side of the current collector 5 by a wet process;
[0068] (2) The pore-forming needle 41 made of flexible fiber is vertically immersed in the electrode slurry 6 (such as Figure 2A);
[0069] (3) drying the electrode slurry;
[0070] (4) When the liquid content in the electrode slurry is 5-10wt% (at this time the electrode slurry is about to be completely dry), pull out the pore-making needle (such as Figure 2 B), after the electrode slurry is completely dried, an active material layer with vertical pores is obtained. The surface schematic diagram of the active material layer is shown in Figure 4 As shown;
[0071] (5) After coating the electrode slurry on the surface of the other side of the current collector, repeat the above steps (2)-(4) to obtain an electrode, which includes a current collector and active material layers located on both sides of the current collector. When the electrode is a positive electrode sheet, the active material layer is a positive electrode active material layer; when the electrode is a negative electrode sheet, the active material layer is a negative electrode active material layer.
[0072] In the pore-making process of the present invention, the immersed volume of the pore-making needle is equivalent to the volume of the vertical hole, so the total pore area ratio required by the design can be achieved by accurately controlling the ratio of the immersed area of the pore-making needle to the area of the electrode slurry.
[0073] The cross-section of the vertical hole in the thickness direction can be designed as required. Figures 7 to 11 Schematic cross-sectional views of five specific embodiments of the electrode of the present invention in the thickness direction. Figure 7 It shows that the cross-section of the vertical hole is rectangular. Figure 8 The vertical hole cross-section is triangular. Figure 9-11 It shows that the cross-section shape of the vertical hole is cone-like.
[0074] Reference Figure 5 , which is a schematic diagram of continuous production of electrode pore formation according to the present invention. Figure 5The motion joints shown in the figure are adjustable up and down. From left to right, the motion joints are named as the first motion joint, the second motion joint, the third motion joint, the fourth motion joint, the fifth motion joint and the sixth motion joint. The relative position of the pore-making needle and the active material layer is controlled by adjusting the relative height of the two adjacent motion joints. For example, in the insertion stage of the pore-making needle, the first motion joint and the second motion joint are kept in a horizontal position and the height is lowered at the same time, so that the depth of the pore-making needle immersed in the electrode slurry can be controlled. In the drying stage, it is only necessary to ensure that the height of the second motion joint and the third motion joint remains unchanged, and its forward movement speed is consistent with the movement speed of the current collector, so that the pore-making needle can be kept stationary relative to the electrode slurry, so that the vertical hole formed on the electrode slurry is consistent with the shape of the pore-making needle; in the process of relative movement and standing, the solvent in the electrode slurry is gradually baked and evaporated. In the stage of pulling out the pore-making needle, that is, when the electrode slurry is about to be completely dried, the fifth motion joint and the sixth motion joint are raised in height, and the relative position of the motion joint and the electrode slurry is enlarged, so that the pore-making needle can be pulled out of the electrode slurry, thereby leaving a vertical hole on the surface of the active material layer. When the electrode slurry is about to be completely dry, the pore-forming needle is pulled out. At this time, the electrode slurry still contains 5-10wt% solvent. The electrode slurry has a certain flexibility and will not wrap the pore-forming needle when pulled out, which will cause the pore-forming needle made of flexible fibers to be unable to be pulled out or damage the fibers, and will not cause the vertical pores to collapse. The movement speed of the current collector at each stage can be controlled by the roller. By controlling Figure 5 The motion joint shown can adjust the height of the local part of the pore-making system, so as to realize the local immersion / extraction of the pore-making needle into / from the electrode slurry, and control the corresponding hole depth, so as to realize the continuous production of electrode pore-making.
[0075] The lithium-ion batteries involved in the following embodiments and comparative examples include the battery cell structure described above: the battery cell structure has 30 layers of negative electrode sheets and 29 layers of positive electrode sheets; the thickness of the negative electrode active material layer 22 located on both sides of the negative electrode current collector 21 is the same, both are 50 μm; the thickness of the positive electrode active material layer 32 located on both sides of the positive electrode current collector 31 is the same, both are 60 μm; the formula of the positive electrode active material layer includes 95 parts of nickel cobalt manganese oxide (NCM811), 2 parts of conductive agent (conductive carbon black Super-P), and 3 parts of polyvinylidene fluoride; the formula of the negative electrode active material layer includes 96 parts of graphite, 1 part of conductive agent (conductive carbon black Super-P), 0.5 parts of carbon nanotubes, 1.5 parts of styrene-butadiene rubber, and 1 part of sodium carboxymethyl cellulose; the positive electrode current collector is aluminum foil with a thickness of 13 μm; the negative electrode current collector is copper foil with a thickness of 6 μm; the cross-sectional area of the positive electrode active material layer is 97 mm×296 mm, and the cross-sectional area of the negative electrode active material layer is 100 mm×300 m. The positive electrode sheets and the negative electrode sheets are stacked. After stacking, the battery cell structure is subjected to manufacturing processes such as welding, packaging, baking, liquid injection, infiltration, formation, capacity division, and appearance inspection to prepare a lithium-ion battery for standby use. In the embodiments and comparative examples, the positive electrode sheets are prepared by a wet process, and the electrode slurry used is a positive electrode active slurry, which is obtained by mixing the formula of the positive electrode active material layer with N-methylpyrrolidone, and the amount of N-methylpyrrolidone added is 30% of the slurry weight; the negative electrode sheets are also prepared by a wet process, and the electrode slurry used is a negative electrode active slurry, which is obtained by mixing the formula of the negative electrode active material layer with water, and the amount of water added is 50% of the slurry. In the process of preparing lithium-ion batteries, except for the different preparations of the positive and negative electrode sheets, the other steps of the embodiments and comparative examples are exactly the same.
[0076] Example 1
[0077] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 0.03%, and the pores are evenly distributed on the electrode (1 / mm 2 ).
[0078] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer,
[0079] The aperture of the negative electrode sheet is equal to the aperture of the positive electrode sheet, and the centers of the holes of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0080] Example 2
[0081] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to 50% of the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 0.03%, and the pores are evenly distributed on the electrode (1 / mm2 ).
[0082] The negative electrode material is prepared into an electrode slurry, and the electrode manufacturing method of the present invention is used to prepare a negative electrode sheet: the pore depth is equal to 50% of the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0083] Example 3
[0084] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 0.01%, and the pores are evenly distributed on the electrode (0.3 pores / mm 2 ).
[0085] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0086] Example 4
[0087] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the manufacturing method of the electrode of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 0.31%, and the pores are evenly distributed on the electrode (10 / mm 2 ).
[0088] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0089] Example 5
[0090] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the manufacturing method of the electrode of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 3.14%, and the pores are evenly distributed on the electrode (100 / mm 2 ).
[0091] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0092] Example 6
[0093] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the manufacturing method of the electrode of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 10 μm, the total pore area ratio is 10%, and the pores are evenly distributed on the electrode (318 / mm 2 ).
[0094] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0095] Example 7
[0096] The positive electrode material is prepared into an electrode slurry, and the positive electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore radius is 3.1 μm, the total pore area ratio is 0.03%, and the pores are evenly distributed on the electrode (10 / mm 2 ).
[0097] The negative electrode material is prepared into an electrode slurry, and the negative electrode sheet is prepared by the electrode manufacturing method of the present invention: the pore depth is equal to the thickness of the active material layer, the pore diameter of the negative electrode sheet is equal to the pore diameter of the positive electrode sheet, and the pore centers of the positive electrode sheet and the negative electrode sheet are completely aligned.
[0098] Comparative Example 1
[0099] The positive electrode material is prepared into an electrode slurry, coated on the surface of the positive electrode current collector, and then dried to form a positive electrode sheet.
[0100] The negative electrode material is prepared into an electrode slurry, coated on the surface of the negative electrode current collector, and then dried to form a negative electrode sheet.
[0101] Comparative Example 2
[0102] The positive electrode material is prepared into an electrode slurry, coated on the surface of the positive electrode current collector, and then dried to form a positive electrode sheet. The active material layer on both sides of the positive electrode sheet is mechanically punched to make the hole depth equal to the thickness of the active material layer, the hole radius is 10 μm, the total hole area ratio is 0.03%, and the holes are evenly distributed on the electrode (1 / mm 2 ).
[0103] The negative electrode material is prepared into an electrode slurry, coated on the surface of the negative electrode current collector, and then dried to form a negative electrode sheet. Mechanical punching is used on the active material layer on both sides of the negative electrode sheet so that the hole depth is equal to the thickness of the active material layer, the hole diameter of the negative electrode sheet is equal to the hole diameter of the positive electrode sheet, and the hole centers of the positive and negative electrode sheets are completely aligned.
[0104] Comparative Example 3
[0105] The positive electrode material is prepared into an electrode slurry, coated on the surface of the positive electrode current collector, and then dried to form a positive electrode sheet. Laser etching is used on the active material layer on both sides of the positive electrode sheet to make the hole depth equal to the thickness of the active material layer, the hole radius is 10 μm, the total hole area ratio is 0.03%, and the holes are evenly distributed on the electrode (1 / mm 2 ).
[0106] The negative electrode material is prepared into an electrode slurry, coated on the surface of the negative electrode current collector, and then dried to form a negative electrode sheet. Laser etching is used on the active material layer on both sides of the negative electrode sheet to make the hole depth equal to the active material layer thickness, the pore diameter of the negative electrode sheet equal to the pore diameter of the positive electrode sheet, and the hole centers of the positive and negative electrode sheets are completely aligned.
[0107] The batteries prepared in the examples and comparative examples were tested to measure their energy density, charging capacity, discharge power and cycle life. The results are shown in Table 1.
[0108]
[0109] The battery is cycled at a rate of 1C, and the number of cycles experienced when the capacity retention rate decays from the initial 100% SOH to 80% SOH is the cycle life. It can be seen from the results in Table 1 that after the electrode is designed by this invention, the cycle life, battery short circuit rate (i.e.: number of battery short circuits / number of tests) and discharge power of the battery are significantly optimized. Increasing the aperture of the vertical holes of the electrode and increasing the total pore area ratio can significantly improve the discharge power capacity of the battery, but has no significant effect on the energy density.
Claims
1. A method for manufacturing an electrode, characterized in that: The following steps are involved: S1, coating the electrode slurry on the surface of one side of the current collector by a wet process; S2, vertically immersing a pore-making needle made of flexible fibers into the electrode slurry; S3, drying the electrode slurry; S4, when the liquid content in the electrode slurry is 5-10wt%, the pore-forming needle is pulled out, and after the electrode slurry is completely dried, an active material layer with vertical pores is formed on the surface of the current collector; S5, after coating the electrode slurry on the surface of the other side of the current collector, repeat the above steps S2-S4 to obtain an electrode, which includes a current collector and active material layers located on both sides of the current collector.
2. The method according to claim 1, characterized in that: The vertical cross section of the pore-making needle is one or more of a circle, a rectangle, a diamond, and a triangle.
3. The method according to claim 2, characterized in that The vertical cross section of the pore-making needle is circular, and its diameter is between 1 and 500 μm.
4. The method according to claim 1, characterized in that The immersion area of the pore-making needle is 0.01%-10% of the area of the electrode slurry.
5. The method according to claim 1, characterized in that: The immersion depth of the pore-making needle is 0-100% of the thickness of the electrode slurry, and the immersion depth can be adjusted according to actual needs.
6. The method according to claim 1, characterized in that The surface of the pore-making needle has a hydrophobic coating or an oleophobic coating, and the hydrophobicity or oleophobicity of the coating is opposite to the hydrophobicity or oleophobicity of the electrode slurry.
7. The method according to claim 1, characterized in that The immersion depth of the pore needle is adjusted by a plurality of motion joints.
8. The method according to claim 1, characterized in that The motion joint and the pore-forming needle are integrated on the pore-forming system. The pore-forming system has two upper and lower rows of pore-forming needles. The motion joint is located at both ends of the pore-forming system and in the middle of the upper and lower rows of pore-forming needles.
9. An electrode, characterized in that: The method is prepared by any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the electrode according to claim 9.
Citation Information
Patent Citations
Electrode pole plate of lithium ion battery, pole plate rolling device and lithium ion battery
CN106531961A
Preparation method of high-safety and high-performance lithium battery negative electrode
CN109817895A
Preparation method of pole piece, and lithium battery
CN113745448A
Thick electrode plate, preparation method thereof and battery
CN115275094A
High-capacity long-circulation sodium ion battery
CN117954635A